2010
DOI: 10.1007/s12630-010-9356-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactate flux during carotid endarterectomy under general anesthesia: correlation with various point-of-care monitors

Abstract: Purpose The ability to assess the brain-at-risk during carotid endarterectomy (CEA) under general anesthesia remains a major clinical problem. Point-of-care monitoring can potentially dictate changes to management intraoperatively. In this observational study, we examined the correlation between a series of point-of-care monitors and lactate flux during CEA. Methods Both neurosurgeons and vascular surgeons participated in the study. The patients underwent arterialjugular venous blood sampling for oxygen, carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Similarly, rScO 2 correlates to SjvO 2 (Williams et al, 1994b; Grubhofer et al, 1997; Espenell et al, 2010) and a correlation to stump pressure is also reported (Kragsterman et al, 2004; Yamamoto et al, 2007; Lee et al, 2008; Manwaring et al, 2010; Tambakis et al, 2011) so that a low stump (<40 mmHg) results in a large change in rScO 2 (Tambakis et al, 2011) but the relationship might be absent in a large series of patients (Pedrini et al, 2012). rScO 2 and systemic blood pressure correlate, with higher pressures leading to better oxygenation values (Williams et al, 1994c; Ritter et al, 2011).…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, rScO 2 correlates to SjvO 2 (Williams et al, 1994b; Grubhofer et al, 1997; Espenell et al, 2010) and a correlation to stump pressure is also reported (Kragsterman et al, 2004; Yamamoto et al, 2007; Lee et al, 2008; Manwaring et al, 2010; Tambakis et al, 2011) so that a low stump (<40 mmHg) results in a large change in rScO 2 (Tambakis et al, 2011) but the relationship might be absent in a large series of patients (Pedrini et al, 2012). rScO 2 and systemic blood pressure correlate, with higher pressures leading to better oxygenation values (Williams et al, 1994c; Ritter et al, 2011).…”
Section: Resultsmentioning
confidence: 97%
“…In addition, prior work has indicated that meaningful alterations in cerebral saturation can be determined in this manner, for example, pre-and post-carotid cross-clamping with carotid endarterectomy. 10,11 Lastly, establishing an a priori agreed upon baseline permits true comparisons across the maximal number of studies. 7 In these experiments, we show desaturations using the same type of cerebral oximeter (i.e., CasMed FORE-SIGHT) used by Hemmerling et al 7 This oximeter claims absolute cerebral oximetry, not just documentation of trends.…”
Section: Discussionmentioning
confidence: 99%
“…7 We have also used this monitor to document changes in cerebral saturation with cross-clamping during carotid endarterectomy under general anesthesia. 11 Cardiac output measurement utilizing the FloTrac system has been recently reviewed. 14 This device has been found to provide a good estimate of cardiac output compared with pulmonary artery thermodilution, which is considered the gold standard; however, other work highlights the potential limitation of the currently available minimally invasive cardiac output devices when compared with thermodilution.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral oximetry 16,17 16-Channel EEG 18 Stump pressure 6 Jugular bulb venous oximetry 19,20 Processed EEG 21 Xenon 133 CBF 22 Conjunctival oxygen tension 23 SSEP 9,10 MEP 8 EEG = electroencephalography; SSEP = somatosensory-evoked potentials; MEP = motor-evoked potential; CBF = cerebral blood flow.…”
Section: To Monitor or Not Monitormentioning
confidence: 99%